Measuring Performance and Effectiveness of online E-exam system in the Computer Center at Mosul University - Shaymaa M. Alnaqeeb (Tikrit Journal of Pure Science, 2022)
Recently, educational institutions have resorted to e-learning to train and educate students, especially those who have the desire to develop their scientific levels and develop their skills in quick and inexpensive ways. This paper focuses on measuring the performance of electronic exam systems, which is an important part of the e-learning process, especially the E-exam system used in the Mosul University computer center for examining people who aim to apply for postgraduate studies. The aim of this study is to measure the performance of the electronic examination system in the computer center at the University of Mosul. In this research, a questionnaire was made to measure the success of this system and the extent of users' satisfaction with it and its usefulness to them in performing their electronic exams. An online survey was conducted using a Google form and sent to the participants between August 21, 2021 and October 11, 2021 to find out the satisfaction of the system users. Microsoft Excel 2010 was used to analyze the data and get the results. This study produced several results, the most important of which are: there was a high degree of satisfaction with the E-exam system, reaching 63%; the percentage of neutrality in it was 25%, while rejection was 12%. According to these results, the system gives high confidence to its users.